BENTUK, FUNGSI, DAN MAKNA LELAKAQ SASAK SEBAGAI MEDIA KAMPANYE CALON WALIKOTA MATARAM - Usman Jayadi (Universitas Sebelas Maret, 2018)
Abstract: In Lombok island, Lelakaq Sasak is one of the important culture use to give suggestion to people. Nowdays Lelakaq Sasak use as campaign median to attract constituent like in head village election, legislative, governor and regency election. The goal of this research is to know the segment of how Lelakaq Sasak types, function and Lelakaq Sasak mean in Mataram regency campaign. The method of collecting data in this research are observation, quotation, document and in analysis data use structural analysis and Semiotic for type analysis. Analysis function use approach hermeniutik. The research result that we know the type of Lelakaq Sasak in Mataram regency campaign. Based on structural analysis including theme; advice. Linguistic; Metaphor, perbandingan, Hyperbola. Sounds; Aliterasi and Asonasi Diksi or rau and rimba. Lelakaq Sasak’s function as entertaint, stimulus and advice. The purpose of Lelakaq Sasak is about describe event and feeling. The final result of this research: type, function and purpose of Lelakaq Sasak in Mataram candidate regency election campaign and to give moral value, material, spiritual and people’s visualisation.Key words: type, function and meaning of Lelakaq Sasak in Mataram candidate regency election campaign.